Comparison of RT-qPCR and Nanostring in the measurement of blood interferon response for the diagnosis of type I interferonopathies. (January 2019) - Pescarmona, Rémi; Belot, Alexandre; Villard, Marine; Besson, Laurie; Lopez, Jonathan; Mosnier, Isabelle; Mathieu, Anne-Laure; Lombard, Christine; Garnier, Lorna; Frachette, Cécile; Walzer, Thierry; Viel, Sébastien
Highlights: The panel of ISGs we used for the IFN signature is quite specific for type I IFN. RT-qPCR and Nanostring are two comparable methods to perform the IFN signature. IFN signature has a strong negative predictive value for interferonopathie diagnosis. IFN signature could be used to monitor patients treated by drugs targeting type I IFN pathway. Abstract: Type I interferonopathies are characterized by an increase of circulating type I interferon (IFN) concentration. Type I interferonopathies refer to rare Mendelian genetic disorders such as Aicardi-Goutières Syndrome (AGS) as well as more frequent and polygenic auto-immune diseases like systemic lupus erythematosus (SLE). Yet, detection of type I IFN in these patients remains challenging as its amount is usually very low in patients' sera. Thus, the detection of interferon-stimulating genes has been proposed as an alternative for the detection of this cytokine but sensitivy, specificity and predictive values of the assay have not been reported so far. In this study, we propose two different methods based on Nanostring or RT-qPCR to measure in the clinical routine the IFN response, defined as a set of transcripts that are systemically induced by IFNs. The IFN signature is composed of 6 IFN stimulated genes (ISGs) and has a strong predictive value for the diagnosis of type I interferonopathies. The use of this simple test might represent a gold standard for the evaluation of various autoimmune diseases. Moreover, this test could also be used to monitor patients treated with drugs targeting type I IFN pathway. When comparing both methods - Nanostring and qPCR - in terms of analytical performance, they provided similar results but Nanostring was quicker, easier to multiplex, and almost fully-automated, which represent a more reliable assay for the daily clinical practice.